Insect galls of a protected remnant of the Atlantic Forest tableland from Rio de Janeiro State (Brazil) - Maia,Valéria Cid (2016)
ABSTRACT Insect galls of a protected remnant of the Atlantic Forest tableland from Rio de Janeiro State (Brazil): Galling insects in Rio de Janeiro state are known by their great diversity, despite most of the surveys have been done in restinga. This paper investigated the insect galls from a remnant of Atlantic Forest located in São Francisco de Itabapoana municipality, Rio de Janeiro state, Brazil. The galling insect fauna was surveyed from March, 2013 to April, 2014 at the Estação Ecológica Estadual de Guaxindiba. 143 gall morphotypes were found in 31 plant families, 60 genera and 82 species. Fabaceae, Myrtaceae and Sapindaceae were the main host families, being Trichilia, Tontelea and Eugenia the main host genera. Most galls occured on leaves, with globose shape, green and glabrous. Diptera (Cecidomyiidae), Hemiptera, and Lepidoptera were the inducing orders and the associated fauna comprised parasitoids (Hymenoptera), inquilines (Lepidoptera, Coleoptera, and Hemiptera: Coccoidea), successors (Psocoptera, Collembola and Acari), and predators (Pseudoscorpiones). Three plant genera and nine plant species are recorded for the first time as host of galls in Brazil. All the records are new to the municipality, and the distribution of 15 galling species is extended to the North of the state of Rio de Janeiro.